2023
DOI: 10.3389/fendo.2023.1096050
|View full text |Cite
|
Sign up to set email alerts
|

The female upper reproductive tract harbors endogenous microbial profiles

Abstract: IntroductionThe female reproductive tract harbours unique microbial communities (known as microbiota) which have been associated with reproductive functions in health and disease. While endometrial microbiome studies have shown that the uterus possesses higher bacterial diversity and richness compared to the vagina, the knowledge regarding the composition of the Fallopian tubes (FT) is lacking, especially in fertile women without any underlying conditions.MethodsTo address this gap, our study included 19 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Compared to the lower reproductive tract and the uterus, there are relatively few studies on the tubal microbiome ( Miles et al., 2017 ; Zhou et al., 2019 ; Walther-António et al., 2016 ; Pelzer et al., 2018a ; Canha-Gouveia et al., 2023 ). Walther-António et al.…”
Section: Composition Of the Female Reproductive Tract Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the lower reproductive tract and the uterus, there are relatively few studies on the tubal microbiome ( Miles et al., 2017 ; Zhou et al., 2019 ; Walther-António et al., 2016 ; Pelzer et al., 2018a ; Canha-Gouveia et al., 2023 ). Walther-António et al.…”
Section: Composition Of the Female Reproductive Tract Microbiomementioning
confidence: 99%
“…In most studies on the tubal microbiome, the selected subjects tended to have benign diseases of the uterus and cervix that may affect the cervical physiological barrier, making it easy for bacteria (such as Lactobacillus ) that colonize the lower reproductive tract to migrate upward ( Walther-António et al., 2016 ; Pelzer et al., 2018a ). A recent study comparing the microbiome of the fallopian tube in women who underwent tubal ligation (normal controls) and those who underwent hysterectomy for benign disease (cases) showed no significant differences in microbial diversity or differential abundance analysis ( Canha-Gouveia et al., 2023 ). It was also found that the most prevalent genera among fallopian tube samples were Lactobacillus , Prevotella , Acinetobacter , Propionibacterium , and Faecalibacterium ( Canha-Gouveia et al., 2023 ).…”
Section: Composition Of the Female Reproductive Tract Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…59 During the transfer of fresh/frozen embryos, the dominance of Lactobacillus in the vagina, cervix and including uterus can have better reproductive outcomes, and the decrease in Lactobacillus at the endometrial level can be associated with worse embryo implantation rates. 39 59 60 61 62 Nevertheless, the presence and dominance of alive Lactobacilli inside the uterus is an active topic of debate, 38 63 64 65 which requires clarification.…”
Section: Fertility Complications and The Lower Reproductive Tract Mic...mentioning
confidence: 99%
“…3 However, it was shown that 70% of the microbial communities of the endometrium and the fallopian tubes (FTs) are shared within a patient. 4 It is acknowledged that the microbiome plays a role in the process of becoming pregnant and maintaining a healthy pregnancy. 5 Consequently, alterations in microbial homeostasis, sometimes referred to as dysbiosis, can lead to various reproductive disorders, ranging from bacterial vaginosis and pelvic inflammatory disease (PID) to infertility and pregnancy complications.…”
mentioning
confidence: 99%